Algorytm regulacji dwuwymiarowego pola temperatury powierzchni obracającego się walca stalowego - Frączyk, Andrzej; Kucharski, Jacek (Wydawnictwo Politechniki Łódzkiej, 2013)
W artykule przedstawiono algorytm regulacji dwuwymiarowego pola temperatury powierzchni obracającego się walca stalowego, nagrzewanego indukcyjnie sześcioma ruchomymi wzbudnikami. W ramach weryfikacji praktycznej opracowanego algorytmu zaprezentowano możliwość uzyskiwania przy jego zastosowaniu dość złożonych dwuwymiarowych rozkładów temperatury.

The paper presents an algorithm for control of 2D temperature of the surface of induction heated rotating steel cylinder. Moving inductors are used as heat sources in the analyzed system. The proposed algorithm has been proven to be an efficient solution by ensuring a quite sophisticated temperature field distribution on the cylinder surface during an experimental verification
The algorithm for 2D temperature field control of the surface of a rotating steel cylinder